Diversifikasi Desain Produk Sentra Keramik Dinoyo Bersumber Ide Budaya Lokal Malang - Ponimin, Ponimin (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2018)
Ceramic craft in Sentra Keramik Dinoyo of Malang has been produced in more or less four generations long. In the beginning, local crafters made potteries in traditional kitchenware. The increasing demand of consumer made room for decorative ceramic. Unfortunately, their product design development didn’t reflect local culture nuance. It because crafters weren’t able to develop the design. Through this activity, researcher tried to solve design problem, extracted from local culture as ceramic creation idea. So that local culture could appear as local ceramic characters. Ceramic product design development is done by formulating design concept, manifesting concept into product design image. Design image result then tested to design expert. The product design image then improved. This design improvement then manifested into ceramic product prototype. This development produced a unique design, one of them is ceramic with ‘Kendi Garuda Kamandalu’ (teapot) from Kidal Temple’s reliefs theme.